Digital Transformation in Financial Management: Security and Efficiency - Wulan Ayuandiani; Fausiah; Muhammad Mukhram; Nurul Listiawati; Indayani B (MultiTech Publisher, 2023)
Digital transformation has changed the business landscape in various sectors, including in the field of financial management. This article aims to explain the role of digital transformation in financial management, focusing on two essential aspects: data security and operational efficiency. Through literature review and case analysis, this article provides deep insights into how companies can adopt digital technologies to protect their data better and improve operational efficiency